Implementation of ChatGPT Training to Enhance Artificial Intelligence Literacy Among First-Year Dental Students - Candra, Agata Iwan; Ali, Mahardi Kamalika Khusna; Tobing, Meyrinda; Gunawan, Ibnu; Indriyasari, Arini; Maharnindra, Dery; Rohmatin, Nur (Jurnal Pengabdian UNDIKMA, 2026)
This community service aims to enhance AI literacy among first-year dental students through a ChatGPT-based training program, resulting in improved understanding of AI concepts, practical skills in using ChatGPT, and critical awareness in assessing its outputs.. A total of 58 students participated, with effectiveness measured through a pre-test and post-test Likert-scale questionnaire covering five indicators: understanding of AI and ChatGPT, application in learning, technical skills, critical validation, and academic confidence. Results showed improvements in all indicators, with the highest increase in technical skills (56.08%) and the lowest in critical validation (29.77%). One-way ANOVA confirmed significant differences among indicators (F = 88.335, p < 0.05). These findings demonstrate that short training can effectively strengthen students’ AI literacy by improving knowledge, technical proficiency, and academic confidence. Nonetheless, the relatively lower gain in critical validation highlights the need for extended guidance in verifying ChatGPT outputs. This program can serve as a practical model for fostering digital literacy in higher education.